The Use of a Performance Assessment for Identifying Gifted Lebanese Students - Sarouphim, Ketty M. (2009)
The purpose of this study was to investigate the effectiveness of DISCOVER, a performance- based assessment in identifying gifted Lebanese students. The sample consisted of 248 students (121 boys, 127 girls) from Grades 3-5 at two private schools in Beirut, Lebanon. Students were administered DISCOVER and the Raven Standard Progressive Matrices (RSPM). Teachers and parents of identified students were interviewed. Results showed evidence for DISCOVER's concurrent validity with RSPM, as correlations between students' DISCOVER ratings in spatial intelligence and their Raven scores were high, whereas correlations between students' DISCOVER ratings in linguistic intelligences and their Raven scores were low. Parents' and teachers' interviews corroborated the results, with a few exceptions. Of the total sample, 14.5% were identified, with no gender differences. The researcher concluded that DISCOVER could be used effectively in Lebanon for identification purposes, but further research is needed to support the findings.